INTERNATIONAL COMMISSION AGAINST IMPUNITY IN GUATEMALA: A NON-TRADITIONAL TRANSITIONAL JUSTICE EFFORT - Nyberg, Tove (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2015)
This paper examines the concept of transitional justice and makes the argument that transitional justice contexts would benefit from embracing a wider range of mechanisms. It uses the International Commission Against Impunity in Guatemala (CICIG) as an example of a non-traditional transitional justice measure and evaluates its mandate, set-up and achievements to show the advantages with a hybrid mechanism in the Guatemalan context.